(untitled) (Journal of actual problems of jurisprudence, 2022)
At present, the spontaneous development of relations with nature endangers the existence of not only individual objects, territories, countries, but also of all mankind. This is explained by the fact that a person is closely connected with wildlife through its material and spiritual needs, that is, humanity as a whole develops and creates a cultural environment on earth, passing on its labor and spiritual experience from generation to generation. In our current conditions, this education should cover a large part of society through general environmental education of people from school walls to university walls. The uniqueness of environmental education lies in its new setting of educational goals, a new approach. In this regard, the most important goal of environmental education is the formation of an ecological culture of a person and society. During the work on the project, the conceptual method, statistical and comparative methods, the historical and legal method, the method of analysis and synthesis, the method of using "big data" were applied. The formation of ecological consciousness is closely connected with ecological education. The growing number of environmental problems, whether they are regional or international in nature or affect the international industry as a whole, require greater cooperation between states and action in the interests of international organizations. The level of environmental and legal culture determines the quality of legal norms, their knowledge, understanding and interpretation in society, as well as the degree of readiness to protect human environmental rights by all legal means, to consistently fulfill environmental tasks in everyday life and professional activities. It is concluded that programs and laws on environmental protection are meaningless until the population has a developed environmental legal awareness and does not participate in the process of implementing the law. Greater public participation can go a long way towards addressing environmental management issues. The dissemination of information is critical to enabling citizens to participate. Key words: environmental law and order, environmental legislation, law and order, environmental law, environmentalism, environmental legal awareness